Changes in haemogram of pulmonary TB patients during positive clinical and radiology improvement - Matsegora, N. A.; Golubenko, N. Yu.; Lekan, O. Ya.; Omelian, L. P. (Journal of Education, Health and Sport, 2016)
Matsegora N. A., Golubenko M. Yu., Lekan O. Ya., Omelian L. P. Changes in haemogram of pulmonary TB patients during positive clinical and radiology improvement. Journal of Education, Health and Sport. 2017;7(1):317-322. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.265776 http://ojs.ukw.edu.pl/index.php/johs/article/view/4217 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. CHANGES IN HAEMOGRAM OF PULMОNARY TB PATIENTS DURING POSITIVE CLІNICAL AND RADIOLOGY IMPROVEMENT N. A. Matsegora, M. Yu. Golubenko, O. Ya. Lekan, L. P. Omelian Odessa National Medical University Summary We studied changes in the complete blood count in 48 patients with infiltrative and disseminated pulmonary tuberculosis before and after treatment against positive clinical and radiographic improvement. The haemogram of patients with tuberculosis varies during the treatment. The mean concentration of haemoglobin in red blood cells and the count of red blood cells in peripheral blood of patients with infiltrative (in 60% of cases) and disseminated (in 45% of cases) tuberculosis increased equally: Hb to 139.5 and 139.3 g/l; RBC to 4.33∙10^12/l and 4.4∙10^12/l, respectively. In 9 (36 ± 9.2%) patients with infiltrative tuberculosis, there was a reduction in the average haemoglobin content in red blood cells of patients to 117.7 g/l, while in disseminated tuberculosis, haemoglobin level did not fall below 132.7 g/l. The obtained results are explained both by a more intensive haematotoxic effect of tuberculosis infection (in case of significant infiltration) and by a toxic adverse effect of prolonged specific chemotherapy, which these patients require. In the haemogram of patients with infiltrative tuberculosis, there was a greater severity of inflammation events, and in disseminated form – of allergic and autoimmune processes. In favourable cases, quantity and quality of blood cells become normal, reflecting the cessation of bacterial excretion, toxicity, and discussion of foci and areas of infiltration. Allergenic or toxic effects of different antibacterial medicines on haematopoiesis cannot be excluded. They often caused eosinophilia, in some cases - leukocytosis, band left shift, lymphocytosis, rarely leukopenia, which may stimulate the lymphoid and reticular reaction. The results indicate the feasibility to add TB chemotherapy with cytoprotective medicines. Key words: haemogram of patients with tuberculosis.